Getting Out From The Back of the Sofa: Sustainable Funding for Open Access Books - Grady, Tom (Septentrio Conference Series, 2023)
Professor Martin Eve pointed out in an article on WonkHE in 2020 that “the biggest blocker to open access for monographs seems to be economic. Book Processing Charges at the €12,000 mark will not scale in disciplines where an entire department’s book purchasing budget is just €8,000”. Three years on and this still seems to hit the nail on the head when thinking about sustainability of funding for open access books. BPCs remain a significant method of paying to produce OA monographs for many researchers and libraries. But in the last three years we have seen several new initiatives emerge that seek to solve the problem posed by funding via BPCs alone. There are now quite a few collective funding models for OA books: they vary in complexity and all work slightly differently but they all offer alternatives to BPCs. At the last two Munin Conferences on Scholarly Publishing, my colleague Professor Eve presented on several of these models, including MIT Press’s D2O, JSTOR’s Path 2 Open and many others, and he also described the model that was his own invention with the COPIM project: Opening the Future. In this workshop we will pick up where Professor Eve left off, giving a brief update on how those models have fared in order to set the scene for discussion. But we’ll then pose a provocative central question that has arisen from this new landscape. All of these models offer a path for academic presses to fund their open access monographs by harnessing the power of small contributions from many member libraries, but how will they achieve sustainability? How will libraries ensure that money for these programmes is in their budget year on year? How will the scholarly publishers ensure a reliable income to produce their OA books? In other words, how can the sector work together to ensure the continued success of non-BPC approaches and ensure that the money for them is not just found ‘down the back of the sofa’? This will be a lively session with lots of Q&A to drill down to the detail of how we, together, can find reliable income streams for the increasingly populous landscape of collective funding initiatives.